The Gift and Ethical Responsibility within Society - Frumensius Gions; Antonius Denny Firmanto; Silvinus Soter Reyaan (Studia Philosophica et Theologica, 2026)
The following research aims to explore the complex and multifaceted meaning of the gift through the inquiries of various scholars. Using the descriptive and analytical approach, this study examines the words associated with the experience of the gift. The guiding question to be elaborated is what the gift means and how it may ground ethical concern. The results of the study show that the word “gift” is polysemous and functions as a moral category of relation, expressed through generosity, recognition, and communion. The noun “gift”, rooted in the verb “to give”, corresponds to the ideas of donum, munus, and charis. As a relational category, the gift is constituted by the giver, the receiver and the given object, but ultimately reflects God’s grace that sustains human acts of living hospitably in koinonia. This research suggests that the gift, rooted in God’s own self-giving love, provides a foundation for the ethical concern as persons called to communion and discipleship in Christ. Acknowledging that gift is not a private possesion but a relational reality, this study contributes to moral responsibility and social commitment.